Ageing and multisensory integration: A review of the evidence, and a computational perspective. (May 2021) - Jones, Samuel A.; Noppeney, Uta
Abstract: The processing of multisensory signals is crucial for effective interaction with the environment, but our ability to perform this vital function changes as we age. In the first part of this review, we summarise existing research into the effects of healthy ageing on multisensory integration. We note that age differences vary substantially with the paradigms and stimuli used: older adults often receive at least as much benefit (to both accuracy and response times) as younger controls from congruent multisensory stimuli, but are also consistently more negatively impacted by the presence of intersensory conflict. In the second part, we outline a normative Bayesian framework that provides a principled and computationally informed perspective on the key ingredients involved in multisensory perception, and how these are affected by ageing. Applying this framework to the existing literature, we conclude that changes to sensory reliability, prior expectations (together with attentional control), and decisional strategies all contribute to the age differences observed. However, we find no compelling evidence of any age-related changes to the basic inference mechanisms involved in multisensory perception.